Research of psychological and pedagogical conditions for the formation of personal and professional identity of vocational students - Nataliia Fedorivna Shevchenko; Olena Serhiivna Volobuyeva; Maria Heorhiivna Ivanchuk (Insight: the psychological dimensions of society, 2023)
The purpose of this article is to highlight psychological and pedagogical conditions for the formation of personal and professional identity of vocational students. Methods. To achieve the purpose, a set of research methods was used, involving theoretical ones: analysis, comparison, systematization, generalization of literary scientific sources, and experimental research data; empirical: psychodiagnostic methods “Individual socio-professional demand” (B. Yasko, Ye. Kharytonova), “Technique for studying personal identity” (L. Schneider), “Reflexivity development test” (A. Karpov), “Multidimensional and functional responsibility test (OTV-70)” (V. Priadein), “Professional readiness” (A. Cherniavska), “Methodology for diagnosing behavioral activity type” (L. Vasserman, N. Humeliuk); mathematical and statistical methods. Results. An empirical research of psychological and pedagogical conditions for the formation of personal and professional identity of vocational students is presented. The analysis of attitudes toward belonging to a professional community showed that the respondents lack formed attitude toward themselves and the values of the chosen field of expertise. The study of self-perception as a subject of professional activity proved that the respondents are characterized by fairly high professional self-esteem and are satisfied with the attitude of others to them as professionals. The responsibility test results indicated neutrality, a situational manifestation of responsibility and independence, and the need for additional control to finish the job. The examination of reflexivity demonstrated a difference in indexes depending on professional specialization, namely: the indexes of future specialists in service industry are much higher; the respondents are more focused on communicating with others; interpsychic reflexivity correlates with the ability to understand other people; they conceptualize their personality from the perspective of professional activity. Diagnostics of motivational activity for professional self-actualization established its insufficient development. A correlation analysis was carried out to establish available connections between separated conditions and the structural components of personal and professional identity. Conclusions. It is confirmed that the formation of vocational students’ personal and professional identity can be determined by the following psychological and pedagogical conditions: emotional and positive perception of belonging to a professional community, positive self-perception as a subject of professional activity, a high level of responsibility, the availability of a reflective space, and the development of motivation for professional fulfilment.